Equity and Efficiency When Needs Differ - Kristoffer Berg; Morten Håvarstein; Paolo Piacquadio (CESifo GmbH, 2024)
There is no consensus on how to measure social welfare and inequality when households have different needs. As we show, a dilemma emerges between holding households responsible for their needs or compensating them. This dilemma is of first-order importance for social welfare, but generally plays a minor role in the measurement of inequality. To address this impasse, we introduce partial compensation. Our axiomatic characterizations reveal novel families of welfare criteria and, with the extension to multidimensional commodity spaces, provide ready-to-use criteria for the analysis of redistributive policies.
Keywords: D30; D63; I31; 330; household needs; transfer principles; equity-efficiency trade-off; welfare criteria